Electronic Multimodel-based Instructional Materials Development on the Sound Wave Topic Incorporating the Verses of the Quran - Muhammad Choirul Hadi Santoso; Zainuddin Zainuddin; Mastuang Mastuang (Universitas Lambung Mangkurat, 2023)
This research aims to produce multimodel-based electronic instructional materials on sound waves incorporating the verses of the Quran to improve learning outcomes. This research aims to describe the validity, practicality, and effectiveness of the instructional materials. The method employed was research and development. The model of research and development used was the ADDIE model. The pre-experiment design (the one-group pretest-posttest design) was conducted. The subjects of the tryout test consisted of 33 students of XI MIPA 4 MAN 2 Banjarmasin. The data were collected through validity assessment instruments, questionnaires, and learning achievement tests. The results of the research showed that: (1) the lesson plan validity of 3,44 is very good; the validity of the student worksheet of 3.27 category is good; the validity of the instructional material of 3.30 was good; and the validity of achievement test of 3.33 was good, (2) the practicality of the instructional materials with an average score of 3.33 was a good category, and (3) the effectiveness of instructional materials with an average score of 0.75 was a high category. It can be concluded that multimodel-based electronic instructional materials on sound waves incorporating the verses of the Quran are applicable in learning. Thus, the instructional materials developed can be used as alternative materials to improve learning outcomes.